Human Expressions of Object Preference Affect Dogs’ Perceptual Focus, but Not Their Action Choices - Kubinyi, Enikő; Szánthó, Flóra; Gilmert, Elodie; Iotchev, Ivaylo B.; Miklósi, Ádám (Frontiers in Psychology, 2020)
Inspired by work on infants, we investigated whether dogs’ behaviours are guided by human displays of preference, contrasting with the animals’ own choices. In a rewarded fetching task, dogs override their own interest toward ‘disgusting’ objects and retrieve what the owner prefers. However, in previous research, both objects were inherently neutral to the dogs and they might have chosen the owner’s object because a ‘happy owner’ predicts a positive outcome. If dogs are indeed able to override their own interests, we expected them to fetch the owner’s object even if (1) they would prefer another one and (2) do not receive a reward for it. Two objects were compared, a toy (hoop) and a bracelet. After establishing that the toy was preferred by all dogs in an initial test of preference, we applied a two-choice procedure to test if either fetching or looking at the objects from a distance would be affected by the owner’s choice. In Study 1, the owner demonstrated happiness toward the bracelet and disgust toward the toy with both facial and body gestures accompanied by verbalizations. Then the owner asked the dog to fetch, without providing additional guiding cues. All dogs fetched the toy, indicating that their own choice was not overcome by the positive emotional state signalled by the owner. To avoid direct contact with the objects, in Study 2 we placed the objects on an unreachable spot after the emotion demonstration and measured the duration of looking at the objects. In the ‘bracelet’ (non-matching) group the owners demonstrated happiness toward the bracelet and disgust toward the toy, similar to Study 1. In the ‘toy’ (matching) group the owners showed happiness toward the toy and disgust toward the bracelet. When the objects were placed on the unreachable spot, dogs looked at both objects for the same amount of time in the non-matching group, but longer at the toy in the matching group. Although the studies did not demonstrate that dogs override their own preferences for an object, the results suggested that the owners’ expressed preference was perceived by the dogs and guided their perceptual focus.